2016
DOI: 10.3892/ol.2016.5178
|View full text |Cite
|
Sign up to set email alerts
|

EHHM, a novel phenolic natural product from Livistona chinensis, induces autophagy-related apoptosis in hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) ranks the second cause of cancer-associated mortality worldwide. In the present study, the effects and mechanisms of a new phenolic natural product E-[6′-(5′-hydroxypentyl)tricosyl]-4-hydroxy-3-methoxycinnamate (EHHM) isolated from Livistona chinensis on the growth of HCC cells were investigated. It was observed that EHHM treatment significantly suppressed cell proliferation and colony formation, and induced cell apoptosis via a mitochondria-dependent caspase pathway in HepG2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Many evidences indicate that miRNAs, by acting either as oncogenes or tumour suppressors, are involved in the process of HCC tumorigenesis and development through the modulation of the autophagic signalling networks [ 54 , 55 ]. miR-181a was reported to repress autophagy in HCC by targeting pro-autophagic protein Atg5, leading to the reduction of apoptosis of HCC cells and acceleration of hepatoma growth [ 56 ]. A significant decrease in miR-7, which induces autophagy by targeting mTOR, was observed in tumour tissue compared to normal tissue suggesting its potential antitumor role in HCC [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many evidences indicate that miRNAs, by acting either as oncogenes or tumour suppressors, are involved in the process of HCC tumorigenesis and development through the modulation of the autophagic signalling networks [ 54 , 55 ]. miR-181a was reported to repress autophagy in HCC by targeting pro-autophagic protein Atg5, leading to the reduction of apoptosis of HCC cells and acceleration of hepatoma growth [ 56 ]. A significant decrease in miR-7, which induces autophagy by targeting mTOR, was observed in tumour tissue compared to normal tissue suggesting its potential antitumor role in HCC [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A naturally occurring substance, hydroxycinnamates or E-[6'-(5'-hydroxypentyl) tricosyl]-4-hydroxy-3-methoxycinnamate (EHHM), is acquired from Livistona chinensis. It has been reported that autophagy enhances cell longevity in HCC cells administered EHHM; EHHM could therefore be a potentially efficacious strategy for treatment of this tumor [500].…”
Section: Targeting Autophagymentioning
confidence: 99%
“…Quercetin Autophagy [483,611] Resveratrol Autophagy [458,480,492,494,612,637-647] [458,480,494,612,637-641] Anthocyanins Autophagy [499] Hydroxycinnamates Autophagy [500] Berberine Autophagy [486,501,[503][504][505]594,595,648,649] Epigallocatechin-3-gallate Autophagy [534,538,539,650] Curcumin Autophagy [515,[517][518][519][520]522,523,[651][652][653][654] Fangchinoline Autophagy [525] Ginsenosides Autophagy [329,[526][527][528][529][530][531][532][533] Terpenoids Autophagy [358,535,536] Triptolide Autophagy [568,570,655] Betulinic acid Autophagy [547,548]...…”
Section: Compound Name Target Referencementioning
confidence: 99%
“…FLC was found to be enriched in natural polyphenolics consisting of flavonoids, phenols, lignans, and anthraquinones [8]. Pharmacological studies showed that FLC possessed antioxidant, antitumor, and hepatoprotective effects [7,[9][10][11][12][13][14][15][16][17]. Due to the huge production of FLC and diverse biological activities of the polyphenols in FLC, their potential edibleness needs to be exploited.…”
Section: Introductionmentioning
confidence: 99%